2022
DOI: 10.33472/afjbs.4.1.2022.94-107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salinity stress on the Phaseolus vulgaris L. plant

Abstract: Soil salinity is one of the world's most important problems. Many studies have tried to find a solution to this problem. Therefore, this report aimed to determine the tolerance of salt concentrations for pole bean (Phaseolus vulgaris L.) plant growth naturally. The current experiment examined the effect of irrigation with saline water on seed germination and seedling growth. Seeds were grown in media containing 0.0, 50, 100, 150, and 200 mM NaCl. Therefore, the number of germinated seeds decreased according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…According to the results of the present research, increasing the level of salinity and humic acid showed an increase in the amount of total soluble carbohydrates in grafted and ungrafted cucumber compared to the control. In the conditions of salt stress, the increase in the amount of total solution carbohydrates is due to the cellular osmotic regulation, and the control of the osmotic and water potential within the cell 74 . Moreover, total soluble carbohydrates play an important role in chelating Na + ions 75 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the present research, increasing the level of salinity and humic acid showed an increase in the amount of total soluble carbohydrates in grafted and ungrafted cucumber compared to the control. In the conditions of salt stress, the increase in the amount of total solution carbohydrates is due to the cellular osmotic regulation, and the control of the osmotic and water potential within the cell 74 . Moreover, total soluble carbohydrates play an important role in chelating Na + ions 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is one of the major abiotic factors that limit the plant productivity and is a major problem in today's irrigation agriculture, as millions of tons of salt are annually dumped on to the soil from the irrigation water (Negroa et al, 2019;Al-huraby, 2022). According to the FAO, (2005), the total global area of salt-affected soils, including saline and sodic soils was 831 million ha (6% of world's total land area).…”
Section: Introductionmentioning
confidence: 99%
“…Buna karşın tuz stresi Pv-12 genotipinin dahil olduğu bazı fasulye genotiplerinde (Pv-11, Pv-13 ve Pv-18) çimlenme homojenitelerinde ise iyileşmelere neden olmuştur (Şekil 5). Yapılan bir çalışmada en yüksek tuz konsantrasyonu olarak uygulanan 200 mM NaCI varlığında çimlendirilen fasulye genotiplerinde tohumların çimlenme oranlarında çok önemli gerilemeler meydana gelmiş[15] ve bu gerilemelerin %83'lere varabileceği rapor edilmiştir[21]. Farklı çalışmalarda aynı tuz konsantrasyonlarında ortaya çıkan farklılıklar bu çalışmanın yapılma amacını teyit eder şekilde tuza toleranslık seviyelerinin kullanılan genotipe bağlı olarak büyük oranda değişebileceğini, çalışma amacına yönelik olarak kullanılacak çeşit ya da genotiplerin her bir çalışmada ayrıca test edilmesi gerektiğiniortaya koymuştur.…”
unclassified